Prevalence of apical periodontitis and root-filled teeth in 2500 panoramic radiographs of a Brazilian population sample - Almeida, Rebecca Dias; Alves, Ana Paula Negreiros Nunes; Brito, Geibson Góis; Soares, Guilherme Costa; Silva, Paulo Goberlânio de Barros; Bezerra, Thâmara Manoela Marinho; Kurita, Lúcio Mitsuo; Costa, Fábio Wildson Gurgel (Journal of Health & Biological Sciences, 2021)
Objective: This study aimed to evaluate the prevalence of teeth with apical periodontitis (AP), root-filled teeth with (RFTAP), and without apical periodontitis (RFT) in 2500 digital panoramic radiographs from an adult Northeastern Brazilian population sample. Methods: A retrospective study was conducted on 2500 panoramic radiographs from a private dental imaging center. Data regarding sex, age, RFT, AP, and RFTAP were collected. A descriptive statistical analysis was performed adopting p<0.05 as significant. Results: The female sex was more significantly associated with RFT and RFTAP than the male sex (p=0,023; p=0.040). The maxilla showed a higher association with RFTAP in the anterior region (p=0.023) and RFT in the posterior region (p=0.023). AP showed a higher prevalence in individuals aged ≥ 31 years (p<0.001). RFTAP showed higher prevalence in the age group 30-70 years (p<0.001). RFT exhibited a significant prevalence in individuals aged ≥21 years (p<0.001). Conclusion: This study showed a higher prevalence of RFT and a low prevalence of AP and RFTAP. Female patients presented a significantly higher prevalence of RFT and RFTAP. Age was an important factor associated with the prevalence of RFT, AP, and RFTAP.